A Glucose-Responsive Hydrogel Inhibits Primary and Secondary BRB Injury for Retinal Microenvironment Remodeling in Diabetic Retinopathy - Zhou, Yue; Zhao, Chan; Shi, Zhiyuan; Heger, Zbynek; Jing, HuaQing; Shi, Zhengming; Dou, Yunsheng; Wang, Siyu; Qiu, Zitong; Li, Nan (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2024)
Current diabetic retinopathy (DR) treatment involves blood glucose regulation combined with laser photocoagulation or intravitreal injection of vascular endothelial growth factor (VEGF) antibodies. However, due to the complex pathogenesis and cross-interference of multiple biochemical pathways, these interventions cannot block disease progression. Recognizing the critical role of the retinal microenvironment (RME) in DR, it is hypothesized that reshaping the RME by simultaneously inhibiting primary and secondary blood-retinal barrier (BRB) injury can attenuate DR. For this, a glucose-responsive hydrogel named Cu-PEI/siMyD88@GEMA-Con A (CSGC) is developed that effectively delivers Cu-PEI/siMyD88 nanoparticles (NPs) to the retinal pigment epithelium (RPE). The Cu-PEI NPs act as antioxidant enzymes, scavenging ROS and inhibiting RPE pyroptosis, ultimately blocking primary BRB injury by reducing microglial activation and Th1 differentiation. Simultaneously, MyD88 expression silence in combination with the Cu-PEI NPs decreases IL-18 production, synergistically reduces VEGF levels, and enhances tight junction proteins expression, thus blocking secondary BRB injury. In summary, via remodeling the RME, the CSGC hydrogel has the potential to disrupt the detrimental cycle of cross-interference between primary and secondary BRB injury, providing a promising therapeutic strategy for DR.
Keywords: Animals; diabetická retinopatie; Retina; Nanoparticles; Blood-Retinal Barrier; Hydrogels; Mice; Cellular Microenvironment; hematoretinální bariéra; nanočástice; myši; retinální pigmentový epitel; buněčné mikroprostředí; Diabetic Retinopathy; modely nemocí na zvířatech; glukosa; Glucose; hydrogely; Retinal Pigment Epithelium; Disease Models, Animal; retina; zvířata